2023
DOI: 10.1111/tpj.16226
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the FERONIA receptor kinase MdMRLK2 enhances apple cold tolerance

Abstract: Cold is one of the main abiotic stresses in temperate fruit crops, affecting the yield and fruit quality of apple in China and European countries. The plant receptor-like kinase FERONIA is widely reported to be involved in abiotic stresses. However, its function in apple cold resistance remains unknown. Modification of cell wall components and accumulation of soluble sugars and amino acids are important strategies by which plants cope with cold. In this study, expression of the apple FERONIA receptor-like kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…RLKs are receptor-like proteins with kinase activity, which can regulate intracellular signaling through phosphorylation, and play an important role in the response to various abiotic stresses. For example, GsLRPK in A. thaliana and the FERONIA receptor-like kinase gene MdMRLK2 in apple ( Malus domestica L.) are involved in cold resistance ( Yang et al., 2014 ; Jing et al., 2023 ). RPK1 in A. thaliana and the leucine-rich repeat receptor-like kinase FON1 in rice are involved in the regulation of drought and water stress, respectively ( Osakabe et al., 2010 ; Feng et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RLKs are receptor-like proteins with kinase activity, which can regulate intracellular signaling through phosphorylation, and play an important role in the response to various abiotic stresses. For example, GsLRPK in A. thaliana and the FERONIA receptor-like kinase gene MdMRLK2 in apple ( Malus domestica L.) are involved in cold resistance ( Yang et al., 2014 ; Jing et al., 2023 ). RPK1 in A. thaliana and the leucine-rich repeat receptor-like kinase FON1 in rice are involved in the regulation of drought and water stress, respectively ( Osakabe et al., 2010 ; Feng et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…They can activate the levels of expression of downstream genes, including COR (cold-regulated), LTI (low-temperature induced), and RD (responsive to dehydration) ( Zhu et al., 2007 ), which thereby improves the ability of plants to tolerate low temperatures. Other TFs, such as NAC1 ( Ma et al., 2013 ; Yin et al., 2024 ) and CAMTAs ( Kim et al., 2013 ), and kinase genes, including VaCPK20 ( Dubrovina et al., 2015 ), GsLRPK ( Yang et al., 2014 ), and the FERONIA receptor-like kinase gene MdMRLK2 ( Jing et al., 2023 ), are involved in this resistance to chilling stress. The development of omics technology enabled plant science researchers to reveal the complex mechanisms of the responses of plants to chilling stress.…”
Section: Introductionmentioning
confidence: 99%
“…FERONIA coordinated plant growth and salt tolerance via the phosphorylation of phytochrome B [55]. Under low temperature stress conditions, the FERONIA receptor kinase MdMRLK2 could enhance the cold tolerance of apple plants by increasing the accumulation of osmoregulatory substances in cells, the synthesis of anthocyanins, and maintaining the stability of cell wall components [56]. Some recent studies in metabolomics have reported that salt stress induced the accumulation of some compounds in D. officinale leaves, especially flavonoids, sugars, and alkaloids, which may play an important role in the salt-stress responses of leaf tissues from D. officinale [22].…”
Section: Discussionmentioning
confidence: 99%
“…It interacts with MdMRLK2, which is a FERONIA receptor-like kinase, to promote the binding of MdMYBPA1 to the promoters of MdANS and MdUFGT , which are key genes involved in anthocyanin biosynthesis. This interaction leads to the activation of their expressions for the accumulation of anthocyanin [ 98 ]. Moreover, MdBBX20 interacts with MdHY5 and enhances the promoter activity of MdMYB1 , which mediates the accumulation of anthocyanin in response to low temperature [ 24 ].…”
Section: Introductionmentioning
confidence: 99%